Deciding Optimal Location of DPFC in Transmission Line Using Artificial Algae Algorithm - Chakravorty, J.; Saraswat, J. (Engineering, Technology & Applied Science Research, 2019)
In this paper, the application of artificial algae algorithm (AAA) in optimal placement distributed power flow controller (DPFC) with MCFC in transmission networks has been proposed The proposed method is tested on IEEE 14- bus system and the results are discussed. The biggest advantage of DPFC is that it can control the active and reactive power flow and bus voltages, simultaneously. In this paper, the optimal placement of one DPFC in IEEE-14 bus system and then optimal placement of two DPFCs in IEEE-14 bus system has been proposed. Optimal placement of DPFC in power system by AAA leads to increased stability and capacity of the power transmission in lines. The proposed model has been simulated in Matlab/Simulink and the performance results are tabulated.